The Evolution of Media Education Methodologies: From ‎Traditional Approaches to Modern Innovations - Jumakulova Nargiza Rakhmatillayevna; Kushieva Nodira Khabibjonovna (WISE Pendidikan Indonesia, 2025)
The rapid expansion of digital technologies has fundamentally transformed media ecosystems and educational practices, prompting the continuous evolution of media education methodologies. This study examines the development of media education from traditional protectionist approaches, which emphasized critical analysis of mass media, to contemporary integrative models that combine critical reflection with digital and multimodal media production. Using a qualitative integrative literature review, this study synthesizes theoretical perspectives, international policy frameworks, and empirical research published between 2015 and 2025. Data were analyzed thematically to identify major methodological shifts, converging paradigms, and persistent challenges in media education. The findings reveal a clear transition from passive, analysis-oriented models toward empowerment-based and participatory approaches that position learners as both critical analysts and active media producers. Contemporary methodologies increasingly integrate critical media literacy with technical and digital competencies, addressing issues such as information evaluation, ethical media use, and digital citizenship in complex, algorithm-driven environments. International frameworks, particularly UNESCO’s Media and Information Literacy initiatives, have played a significant role in shaping these integrative orientations, although their implementation remains uneven across educational contexts. This study contributes an integrative perspective on media education methodologies by linking historical foundations, theoretical debates, policy directions, and classroom practices. The findings underscore the importance of embedding media education as a core, cross-curricular component supported by teacher capacity building and institutional commitment. Such an approach is essential for preparing learners to navigate the challenges of the global information society critically, ethically, and creatively.